Enhancing location estimation accuracy by utilizing time difference of arrival techniques for wireless network - Md Mahyuddin, Mohamad Fahmi (2020)
Mobile communication, which is one of the major areas in telecommunication has been developing rapidly due to the advances of technology in the fields of mobile and wireless communications. Relating to this positioning techniques that focus on detecting user at a very precise location have become common for many applications such as navigation, mobility, emergency services including in the military warfare. Although Global Positioning System (GPS) is the most recognized and widely used positioning system, it has limitations to identify the user’s location, particularly to outdoor location and forest/mountain area. In this context, many geo-location techniques have been proposed as an alternative to GPS. This study aims to propose time difference of arrival (TDOA) techniques that applies the hyperbolic localization method to estimate the location of the user. This technique is an independent platform which can be used with any system or platform, such as unmanned aerial vehicles (UAVs), manned aircraft and ground locations. The development of the algorithm of the TDOA for multiple number of base- station/receiver is developed by referring hyperbolic localization principles. For the purpose of this study, least square estimation techniques are implemented in the TDOA techniques to obtain covariance matrix. Based on the covariance matrix, the accuracy of the estimate mobile/emitter location can be found by using the standard deviation formula. Standard deviation formula act as a parameter for accuracy estimation. Simulation have been conducted to provide a better understanding of the accuracy of TDOA based geo- location systems. The scenario in the simulation involves the effect of noise towards accuracy, the effect of distance towards accuracy, the effect of stationary and moving UAV/receiver, effect of stationary and moving mobile/emitter and optimum distribution of base-station/receiver. All these scenarios were simulated using MATLAB software and each scenario were analyzed for their accuracy. Six hundred simulations with added independent noise were run to acquire an estimate of the mobile/emitter position. The results of the simulation showed that noise and distance have linear effect towards accuracy. The best conditions to achieve optimum accuracy are using with one mobile UAV with the rest stationary of base-stations/receiver. Emitter with the stationary condition is much easier to locate rather than moving emitter as it moves further away from the base-stations/receivers. The best distribution for the base-station is the optimum result for this analysis as it gives a comparison between two dimensional and three dimensional (same and different altitude). The best distribution for base-stations/receivers is in Y-shaped and rectangular formation which gives the best accuracy estimation. For future studies, hybrid positioning can be applied between TDOA and Global Navigation Satellite System (GNSS) or Received Signal Strength Indicator (RSSI) to enhance more accuracy for locating mobile station.